Pembelajaran sejarah berbasis proyek membuat mading digital pada topik Kolonialisme untuk menumbuhkan kecakapan abad ke-21 bagi siswa kelas XI SMAN 3 Blitar - Imam Ropi'i (Universitas Negeri Malang, 2023)
Project-based learning on teaching history makes a digital wall magazine with the theme of colonialism designed for generation Z students who are fluent in IT technology. This article uses a qualitative approach with a descriptive type of research. The research subjects were students of class XI MIPA 2 SMAN 3 Blitar. The application of project-based learning makes students collaborate with their groups to play an active role as planners, implementers, to reporting and evaluating projects for making digital wall boards. Each group is given a main theme and the flexibility to choose the structure or content of the digital magazine, such as infographics, essays, posters, crossword puzzles, to historical memes packaged in contemporary products. Project learning activities for making digital wall magazines encourage students to engage in learning activities that foster 21st century skills, namely information literacy, critical thinking, creative, media and technology literacy, communication, and collaboration.Pembelajaran sejarah berbasis proyek membuat mading digital tema kolonialisme dirancang untuk siswa generasi Z yang fasih teknologi IT. Artikel ini menggunakan pendekatan kualitatif dengan tipe penelitian deskriptif. Subjek penelitian yaitu siswa kelas XI MIPA 2 SMAN 3 Blitar. Penerapan pembelajaran berbasis proyek membuat siswa berkolaborasi bersama kelompoknya berperan aktif sebagai perencana, pelaksana, hingga pelaporan dan evaluasi proyek pembuatan mading digital. Setiap kelompok diberikan tema pokok dan keleluasaan pilihan struktur atau konten mading digital yang dibuat seperti infografis, esai, poster, teka-teki silang, hingga meme sejarah yang dikemas secara kekinian. Kegiatan pembelajaran proyek membuat mading digital memacu siswa terlibat aktivitas pembelajaran yang menumbuhkan kecakapan abad ke-21 yaitu literasi informasi, berpikir kritis, kreatif, literasi media dan teknologi, komunikasi, serta kolaborasi.